Adenomyosis and Adolescence: A Challenging Diagnosis and Complex Management - Francesco Giuseppe Martire; Claudia d’Abate; Giorgia Schettini; Giulia Cimino; Alessandro Ginetti; Irene Colombi; Alberto Cannoni; Gabriele Centini; Errico Zupi; Lucia Lazzeri (Diagnostics)
Adenomyosis is a chronic, hormone-related disease characterized by the presence of the endometrial glands and stroma within the myometrium. This condition can manifest in various features, focal or diffuse adenomyosis or as an adenomyoma, and it may involve different uterine walls (posterior, anterior, and/or lateral walls). The disease can also be classified into different degrees, as mild, moderate and severe, which can be associated with more intense symptoms, although this correlation is not always directly proportional. In fact, adenomyosis can be asymptomatic in about a third of cases or it can significantly impact patients’ quality of life through painful symptoms, such as dysmenorrhea and dyspareunia, abnormal uterine bleeding—particularly heavy menstrual bleeding—and potential effects on fertility. Historically, adenomyosis has been considered a disease primarily affecting premenopausal women over the age of 40, often multiparous, because the diagnosis was traditionally based on surgical reports from hysterectomies performed after the completion of reproductive desire. Data on the presence of adenomyosis in adolescent patients remain limited. However, in recent years, advancements in noninvasive diagnostic tools and increased awareness of this pathology have enabled earlier diagnoses. The disease appears to have an early onset during adolescence, with a tendency to progress in terms of extent and severity over time. Adenomyosis often coexists with endometriosis, which also has an early onset. Therefore, it is important, when diagnosing adenomyosis, to also screen for concomitant endometriosis, especially deep endometriosis in the posterior compartment. The aim of this narrative review is to investigate the prevalence of different types and degrees of adenomyosis in younger patients, assess the associated symptoms, and describe the most appropriate diagnostic procedures for effective therapeutic management and follow-up, with the goal of improving the quality of life for these young women.